Does Passive Leg Activity Influence Oxygen Saturation and Activity in Sedentary Elderly Adults? - Eli Carmeli; Gadi Bartur; Sara Peleg; Shemuel Barchad; Jean-Jacques Vatine (The Scientific World Journal)
This study aimed to investigate whether any physiological changes might have a clinically significant effect on function in sedentary, institutionalized, older adults treated by a passive training program. A total of 18 subjects (mean age 60.7 ± 3.4) with intellectual disability (ID) participated. We measured SpO2 (arterial oxygen saturation) before, during, and after passive training, and used Barthel Index to measure daily living activities. The general trend indicated that inactive people with ID evidenced a continual increase in SpO2% levels and some functional gains during passive treatment, with superiority to manual passive treatment compared to mechanical active passive training. For current clinical practice, most sedentary patients who experience clinically significant deconditioning and desaturation can benefit from passive treatment.